Splenic infarction: Torsion of a wandering spleen in a child - Fatma M. AlSaleh; Salama AlRahoomi; Ghadir J. Jaber; Mamoun AlMarzouqi (Elsevier, 2021)
Torsion of the spleen is a rare etiology of acute abdomen, particularly in children. Presentations may vary as well as diagnostic modalities, therefore a detailed history, thorough physical examination, and a high index of suspicion is necessary. Management may range from observation to splenectomy depending on the presentation and the viability of the organ. In this report we present a pediatric case of splenic torsion in a wandering spleen.